Peran Spesialisasi Auditor dalam Memoderasi Financial Distress dan Komite Audit Terhadap Audit Report Lag - Zulfa Rosharlianti; Euis Lidia Nur Hanifah (Universitas Muhammadiyah Jakarta, 2023)
Objectives. This study aims to investigate the factors that influence the occurrence of audit report lag, considering financial distress and audit committees as the cause, and auditor specialization as a moderating variable.Design/method/approach. This study's population comprises mining companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. A purposive sampling method was employed to select a sample of 229 listed companies. Data analysis involved the use of the multiple linear regression method and the moderated regression analysis.Result/findings. Financial distress and the presence of audit committee are likely to influence the audit report lag. However, it was observed that auditor specialization does not moderate the impact of financial distress and the audit committee on the audit report lag.Theoretical contribution. This study investigates the moderating role of auditor specialization on the impact of financial distress and audit committees on audit report lag. Notably, this simultaneous examination of these variables has not been conducted before.Practical contribution. The findings indicate that both financial distress and the presence of audit committee play crucial roles in ensuring punctual submission of audited financial reports. This punctual reporting helps companies manage their financial condition effectively and enhances the audit committee's effectiveness in improving the punctuality of financial reporting.Limitations. The auditor specialization index in this study exclusively focuses on companies within the mining sector.